PROFESSIONAL TRAINING OF FUTURE TEACHERS OF PHYSICAL CULTURE AS AN IMPORTANT COMPONENT OF PATRIOTIC EDUCATION - Poluliashchenko Iurii (International Journal of Innovative Technologies in Social Science, 2020)
As part of the research, a retrospective analysis of scientific developments on various aspects of professional training of future teachers was made. The state of development of theoretical and methodological bases of professional training of future teachers of physical culture in General and professional readiness for the formation of Patriotic values in particular was revealed. Research in the field of organizing the process of Patriotic education of children and young students, both national and foreign experts, was highlighted. The main goal was to study the theoretical and methodological foundations of developing a system of professional training of future physical culture teachers to form Patriotic values of students in a modern educational institution. Important issues of professional training of future teachers was highlighted. The importance of using modern newest technologies, methods, and educational innovations was proved, using the accumulated national and foreign experience in training a professional. The importance of forming professional competencies of future physical culture teachers was revealed. According to the results of the study, it has been established that recently the interest of national and foreign scientists has only increased in the context of improving the process of forming the professional readiness of future teachers for teaching activities in today’s conditions. As part of the scientific search, we have found that in foreign literature in the context of professional training of future teachers, as well as improving the professional activities of teachers-practitioners, scientific developments on the use of information technologies are carried out using Facebook for the professional development of teachers and students of pedagogical specialties. By identifying the state of development of theoretical and methodological foundations of professional training of future physical culture teachers in General and professional readiness to form Patriotic values in particular, it is established that the scientific achievements of modern national and foreign teachers are mainly focused on such problems as: search for new forms and methods of training in the preparation of future teachers of physical culture in the context of educational reform and increasing requirements for relevant specialists (L. Nikiforova); improving and modernizing the content of professional training of students of physical culture in the conditions of European Integration of national education (P. dzhurinsky, S. Burdyuzha); improving the process of training future specialists in physical culture with the help of innovative approaches and its humanization (R. Akhmetov, V. Shaversky); orientation of the content of professional training of future teachers of physical culture and the use of various forms and methods of training in the field of formation of their readiness to educate physically, mentally, spiritually and socially healthy citizens of Ukraine (L. Sushchenko); development of conceptual provisions for training future specialists in the field of physical culture and sports (N. Stepanchenko); research on the level of confidence and self-efficacy of physical education teachers (E. Öncü); adaptation processes of future physical culture teachers in real conditions of teaching physical culture in secondary education institutions (W. Zayed, M. Zguira, N. Souissi, N. Bali);problems of self-regulation of future teachers of physical culture (S. Kudin) and others.